Integrated energy system region model with renewable energy and optimal control method - Zhang, Feifei; Wang, Yueqiang; Huang, Dong; Lu, Nihui; Jiang, Mintao; Wang, Qi; Luo, Yongheng; Jiang, Fei (Frontiers in Energy Research, 2022)
In the context of global energy transition, integrated regional energy systems containing renewable energy sources play an important role. While improving the economic and carbon efficiency of energy utilization, renewable energy sources also bring research challenges to the safe and reliable operation of energy systems. Based on the region concept, a region model and optimal control method for integrated energy systems containing renewable energy are proposed. Firstly, the key pipeline is taken as the observation object, and the feasible region model of the integrated energy system is determined according to the capacity of key equipment and its pipeline capacity with the multi-energy balance equation as the feasible constraint. Then, considering the mutual backup relationship of different equipment and pipelines, the regional integrated energy system security region model is constructed based on the N-1 security criterion, and the optimal control method based on the region concept is proposed. Finally, the validity of the model is analyzed with arithmetic examples, and the influence of the access capacity and access location of renewable energy on the feasible and safe regions of the regional integrated energy system is discussed. And according to the actual situation of the working state point, the optimal adjustment strategy based on the efficiency function and security constraint is given.